2006
DOI: 10.1590/s0100-879x2006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron overload on the severity of liver histologic alterations and on the response to interferon and ribavirin therapy of patients with hepatitis C infection

Abstract: The objective of the present study was to determine the presence of hepatic iron overload in patients with chronic HCV infection and to correlate it with histologic alterations, HCV genotype and response to therapy. Liver tissue samples from 95 patients with chronic hepatitis C were divided into two groups: group I, presence of iron overload in hepatic tissue (Perls' staining) and group II, no iron overload. Hepatic iron overload was detected in 30 (31.6%) of 95 patients. Of the 69 patients tested by genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
1
16
0
Order By: Relevance
“…There is also increased iron accumulation in all compartments of the liver, similar to what has been reported in various human chronic liver diseases 50,59 and suggested to be a result of the phagocytosis of dead cells, particularly hepatocytes, with local concentration of iron storage products for which there is no excretory mechanism. 12 There was no significant correlation between hepatocyte immunoreactive MDAprotein adduct score and presence and severity of liver injury and inflammation, an unexpected finding that is in contrast to the findings of Spee et al, 60 who found that dogs with chronic inflammatory and cholestatic liver diseases tended to have reduced GSH:GSSG ratios (an alternate indirect indicator of oxidative stress).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There is also increased iron accumulation in all compartments of the liver, similar to what has been reported in various human chronic liver diseases 50,59 and suggested to be a result of the phagocytosis of dead cells, particularly hepatocytes, with local concentration of iron storage products for which there is no excretory mechanism. 12 There was no significant correlation between hepatocyte immunoreactive MDAprotein adduct score and presence and severity of liver injury and inflammation, an unexpected finding that is in contrast to the findings of Spee et al, 60 who found that dogs with chronic inflammatory and cholestatic liver diseases tended to have reduced GSH:GSSG ratios (an alternate indirect indicator of oxidative stress).…”
Section: Discussionsupporting
confidence: 80%
“…32 Similarly, the transitional metal ion iron is associated with chronic liver disease as a result of primary iron overload in hereditary hemochromatosis in humans 46 but also accumulates in chronic liver disease associated with hepatitis C virus 59 and alcohol-related liver disease. 50 The effects of nitric oxide (NO) on hepatocytes are complex and dependent on physiologic context; by itself, NO has been demonstrated to be antiapoptotic for hepatocytes, 11,25,[33][34][35]38,63 but with concurrent oxidative stress, NO potentiates hepatocellular necrosis through the evolution of peroxynitrite, a highly reactive oxygen species that can damage a broad variety of organic molecules producing nitrotyrosine-protein adducts.…”
mentioning
confidence: 99%
“…However, the absence of SVR observed in the group of individuals with this genetic marker was probably not directly related to iron overload, since most studies, so far, failed to report a significant difference in hepatic iron concentration between HCV patients with or without SVR after IFN/RBV treatment (23,25,29,33) . Moreover, therapeutic phlebotomies generally did not increase SVR, indicating that reduction of body iron stores was not associated with treatment outcome (11,21) .…”
Section: Discussionmentioning
confidence: 95%
“…Increased hepatic iron concentration is present in 10% to 36% of patients with chronic hepatitis C (8,9), and hepatic iron overload is even more common among patients with end-stage liver disease due to hepatitis C (10,11). Excess iron deposition in the liver is known to be hepatotoxic and may exacerbate liver injury (12) and be resistant to interferonbased therapy in patients with chronic hepatitis C (13,14); however, little is known about the mechanism of iron accumulation in the liver. We previously reported that transferrin receptor 2 (TfR2), which was recently identified as the second receptor for transferrin (15), was higher in the liver of patients with chronic hepatitis C compared than those with chronic hepatitis B (16).…”
Section: Introductionmentioning
confidence: 99%